Electronic Business-to-Business Marketplace Transformation in the Chemical Industry: Will the Second Wave Succeed Where the First has Failed? - Bee, Tay Kin (Archives of Business Research, 2022)
The global chemical sales are expected to be worth over €6,000 bn by 2030 and this offers a very significant market size for businesses to be transacted electronically. It is generally believed that the first wave of the electronic business-to-business marketplace featured very strongly into the chemical industry sometime in the late 1990’s, but in just over a few years many of these electronic marketplaces started to close down or being merged with others, and later on they too disappeared from the chemical industry. Many of them had failed to sustain themselves in the marketplace and survived. From 2005 onwards, it became apparent that the second wave of electronic marketplaces started to enter the chemical industry again. Electronic marketplaces were being set up by chemical manufacturers and distributors, with many of them even setting up multiple web storefronts, to promote their products. This research will look into the chemical distribution market size, supply chain activities, as well as the various electronic marketplaces present in the chemical industry. The Author will investigate into the reasons why the first wave of chemical electronic marketplaces did not manage to sustain themselves in the market and the possible reasons for their failure. The types of electronic marketplaces during the second wave were investigated in great detail. What are the differences in the types of electronic platforms in the second wave and will they stand a chance to survive this time round, when many of them have failed in the first wave? This research will attempt to investigate the possible strategies through the digital marketplace, by both chemical manufacturers and distributors, in their effort to capture greater market share.